2000
DOI: 10.1001/archfami.9.10.1002
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Medication Costs: A Study of Physician Familiarity

Abstract: Physicians are unfamiliar with the costs of medications they commonly prescribe, and they report that regular access to information on prescription medication costs would help them prescribe more cost-effectively. Arch Fam Med. 2000;9:1002-1007

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 10 publications
2
14
0
1
Order By: Relevance
“…1417 In a recent systematic review of studies of medication cost knowledge, Michael Allan and colleagues 13 found that cost accuracy was generally low, with only 31 percent of physicians’ estimated drug costs falling within 20–25 percent of the actual cost. However, many of these prior studies were limited by ambiguous definitions of actual cost , since the price of a medication often varies by location as well as by prescription plan.…”
Section: Discussionmentioning
confidence: 99%
“…1417 In a recent systematic review of studies of medication cost knowledge, Michael Allan and colleagues 13 found that cost accuracy was generally low, with only 31 percent of physicians’ estimated drug costs falling within 20–25 percent of the actual cost. However, many of these prior studies were limited by ambiguous definitions of actual cost , since the price of a medication often varies by location as well as by prescription plan.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians are unfamiliar with the costs of medications that they commonly prescribe [27], since cost-effective pharmacotherapy evaluation is not yet part of either the clinical practice or the training curricula.Attempts to control or reduce the economic burden of prescriptions are currently being made also in Italy, especially in general practice. However, more efforts need to be made to improve the situation in this context [7,25,28].…”
Section: Discussionmentioning
confidence: 99%
“…15 Lack of adequate physician knowledge about the cost of prescription medications and coverage details of insurance formularies has been identified as primary sources of lack of discussion between patients and physicians. [17][18][19][20][21][22][23][24][25] Given the limited literature on patient-provider communication about medication costs, there is a critical gap in addressing patient concerns about medication costs and affordability. Research is needed to assess the varied sources of knowledge that patients' use to discuss medication cost and affordability.…”
Section: Introductionmentioning
confidence: 99%